Nurturing Lecturer Performance in Maritime Education: The Interplay of Campus Climate, Visionary Leadership and Spiritual Intelligence - Arya Widiatmaja; Adhi Pratistha Silen; Markus Asta Patma Nugraha; Syafni Yelvi Siska; Fauziah Roselia; Vilentina Rosa (LP. Ma'arif Janggan Magetan, 2026)
In maritime education, lecturer performance faces unique challenges because lecturers are expected not only to deliver academic instruction but also to support competency-based training, safety culture, discipline, and industry-aligned professional standards. This study is grounded in the importance of lecturer performance as a key determinant of higher education quality, particularly in maritime education, which requires strong professionalism, resilience, and academic commitment. The study aims to examine the effect of campus climate on lecturer performance with visionary leadership and spiritual intelligence as mediating variables among lecturers at Politeknik Pelayaran Sumatera Barat, Politeknik Ilmu Pelayaran Semarang, and Politeknik Pelayaran Barombong. A quantitative causal design was employed through a survey of 149 lecturers selected using total sampling. The data were analyzed using SEM-PLS with SmartPLS 3 to test validity, reliability, path coefficients, and mediation effects. The findings reveal that campus climate has a positive and significant effect on lecturer performance, visionary leadership, and spiritual intelligence. In addition, both visionary leadership and spiritual intelligence have positive and significant effects on lecturer performance. The results also indicate that visionary leadership and spiritual intelligence significantly mediate the influence of campus climate on lecturer performance. These findings suggest that lecturer performance is shaped not only by a supportive work environment but also by future-oriented leadership and the strengthening of individual spiritual capacity. The study provides practical implications for maritime education institutions in designing policies for competency development, discipline-based work culture, leadership training, and continuous performance improvement that are aligned with maritime education standards and institutional safety values.